The associate [compact disc, unabridged] - Grisham, John (Random House Audio, 2009)
Kyle McAvoy grew up in his father's small-town law office in York, Pennsylvania. He excelled in college, was elected editor-in-chief of The Yale Law Journal, and his future has limitless potential. But Kyle has a secret, a dark one, an episode from college that he has tried to forget. The secret, though, falls into the hands of the wrong people, and Kyle is forced to take a job he doesn't want-- even though it's a job most law students can only dream about. Three months after leaving Yale, Kyle becomes an associate at the largest law firm in the world, where, in addition to practicing law, he is expected to lie, steal, and take part in a scheme that could send him to prison, if not get him killed.